Ventriculoperitoneal shunts: What nurses need to know. Issue 12 (December 2018) - Vacca, Vincent M.
Abstract : Abstract: A ventriculoperitoneal shunt (VPS) is the most common type of implanted cerebrospinal fluid shunt system. Nurses may care for patients who have undergone shunt placement or revision. This article discusses the indications for VPS placement in adults, possible complications, and nursing care for patients following a shunt placement procedure. Abstract : This article discusses the indications for ventriculoperitoneal shunt placement in adults, possible complications, and nursing care for patients following a shunt placement procedure.